Pd and Ni NPs@Eu-MOF, an economically advantageous nanocatalyst for C(sp2)-C(sp2) cross-coupling reactions. Key role of Ni and of the metal nanoparticles. (1st September 2022) - Guo, Jie; Yao, Shan-Xin; You, Li-Xin; Xiong, Gang; Dragutan, Ileana; Dragutan, Valerian; Ding, Fu; Sun, Ya-Guang
Graphical abstract: A heterobimetallic Pd/Ni NPs@Eu-MOF nanocatalyst, consisting of Pd and Ni nanoparticles (NPs) embedded into a porous Eu-MOF was prepared and reached a catalytic yield of over 99% in Suzuki-Miyaura cross-coupling reactions. The advantages of the cost-effective Ni vs . Pd and of NPs over metal ions are highlighted. Abstract: A novel heterobimetallic Pd/Ni NPs@Eu-MOF nanocatalyst, consisting of Pd and Ni nanoparticles (NPs) embedded into a porous Eu-MOF was prepared by solution impregnation followed by H2 reduction. The composite material was fully characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), inductively coupled plasma atomic emission spectroscopy (ICP-AES), powder X-ray diffraction (PXRD) and X-ray photoelectron spectroscopy (XPS). Under optimal reaction conditions the Pd/Ni NPs@Eu-MOF reached a catalytic yield of over 99% in Suzuki-Miyaura cross-coupling reactions. The nanocatalyst is easily recoverable and can be reused for more than five cycles standing proof for high stability and reproducibility. Characterization by PXRD, TEM and XPS of the recovered nanocatalyst confirmed that its initial crystalline structure and morphology have been preserved. The advantages of the cost-effective Ni vs . Pd and of NPs over metal ions are highlighted.